Kajian Kebutuhan Air dan Koefisien Tanaman Padi (Oryza sativa L) di Lahan Rawa Lebak - Triana, Arjuna Neni; Purnomo, Rahmad Hari; Khalid, Feldy (Jurnal Keteknikan Pertanian, 2021)
The purpose of this research is to find out water requirements and coefficient of rice plant in lebak swamp land. The research method used in this study is an experimental method with descriptive data presentation in the form of tables and graphs. The parameters observed included the net water requirements of rice for rice, the evapotranspiration value of plants, the value of crop coefficients and the value of percolation. The results showed that the net water requirements of rice fields were 3.27mm / day, 11,71 6.15 mm / day and 18,75 mm / day. The actual evapotranspiration value (ETc) from the initial growth phase, active vegetative phase, fertilization phase, and seed maturation phase are 1.23 mm / day, 2.57 mm / day, 2.64 mm / day and 1.57 mm / day, while the plant coefficients are 0.42; 0.89; 1,003 and 0,62. The largest evapotranpiration value and plant coefficient is found at the age of growth of 31 to 65 days or the fertilization phase. The percolation value for each stage of growth is 0.27 cm / day, 3.24 cm / day, 4.23 cm / day and 10.63 cm / day.